2D/3D Echocardiographic features of patients with reverse remodeling after cardiac resynchronization therapy. Issue 8 (1st July 2019) - Cimino, Sara; Maestrini, Viviana; Cantisani, Donatella; Petronilli, Valentina; Filomena, Domenico; Gatto, Maria C.; Birtolo, Lucia I.; Piro, Agostino; Lavalle, Carlo; Agati, Luciano
Abstract: Purpose: To describe clinical and echocardiographic characteristics associated with reverse left ventricular (LV) remodeling after 6 months of cardiac resynchronization therapy (CRT) in patients with nonischemic dilated cardiomyopathy. Methods: Twenty‐four consecutive patients underwent 2D and 3D echocardiography before and after 6 months of CRT implant. Several echocardiographic parameters including global longitudinal strain (GLS) and 3D mechanical dyssynchrony (MD) index were calculated. CRT response was defined as a decrease in LV end‐systolic volume (LVESV) of at least 10% at follow‐up. Patients were divided in two groups according to CRT response. Results: Cardiac resynchronization therapy responder (CRTR+) rate was 50%. Nonresponder (CRTR−) patients showed a less significant improvement in NYHA class at follow‐up. At baseline, CRTR− presented with higher LV end‐diastolic volume (LVEDV) ( P = 0.031), LVESV ( P = 0.024), lower left ventricular ejection fraction (LVEF) ( P = 0.002) and less negative GLS ( P = 0.03), and with higher diastolic dysfunction, more impaired right ventricle (RV), and higher pulmonary artery systolic pressure (PASP) ( P = 0.002). No significant differences in echocardiographic parameters of MD were found. Univariate determinants of CRTR+ were LVEF (OR = 1.59, CI 95% = 1.13–2.22, P = 0.007) and TAPSE (OR 1.21, CI 95% = 1.024–1.429, P = 0.025). A ROC curve analysis showed a cutoff value of LVEF of 22.15% significantly related to CRTR+ (SE 80%, SP 50%). Conclusions: Our findings suggest that end‐stage HF patients, presenting before CRT with LVEF <22.15%, may not benefit from the procedure after 6 months. Mechanical dyssyncronicity did not provide additional information to improve candidate selection.